Development of balsem plant (sennega paniculata linn.) nano spray gel as a topical analgesic: Optimization of in vivo efficacy and physical stability - Ismat Marsus; Muhammad Khaerul Nur; Holinda Anggrainy; Yandiono Pongroba (Institute of Computer Science (IOCS), 2026)
The development of natural topical analgesics is constrained by physical instability and limited stratum corneum permeability. Although Senega paniculata L. extract exhibits bioactive potential, its formulation into a calcium-carboxymethyl cellulose (Ca-CMC) nano-spray gel matrix to overcome skin permeability barriers and enhance delivery remains largely unexplored. This study aims to formulate a Ca-CMC nano-spray gel using S. paniculata L. extract across different concentrations (FI 5%, FII 10%, FIII 15%) and to evaluate its preliminary physicochemical properties and analgesic potential in an animal model. Formulations were assessed for stability, physicochemical properties, and chemical interactions. Particle size and polydispersity index were evaluated using Dynamic Light Scattering, while functional groups were analyzed via FTIR. Analgesic efficacy was preliminarily evaluated using an acute thermal pain model to determine the percentage of maximum possible effect. All formulations maintained physiological pH. Formulation FIII exhibited optimal characteristics with a Z-average of 94.6 nm and a polydispersity index of 0.128. FTIR spectra confirmed Ca-CMC ionic cross-linking. In the preliminary animal test, FIII demonstrated an analgesic efficacy of 70.54% (p = 0.958). This study provides preliminary evidence regarding formulation characteristics and preliminary analgesic activity in animals, rather than proving that the product has been fully validated as a clinically effective and stable analgesic formulation. These findings offer a foundational basis for further optimization and development of S. paniculata L. calcium nanocolloids as topical analgesics.